Transcriptomic profile of the northern hard clam (Mercenaria mercenaria) in response to short-term low salinity exposure - Youtsey, Leslie S.; Reece, Kimberly S.; Snyder, Richard A.; McDowell, Jan R. (Frontiers in Marine Science, 2025)
The northern hard clam, Mercenaria mercenaria (Linnaeus, 1758), is an important ecological and economic resource along the U.S. Eastern Seaboard and is primarily limited to salinities above 25 ppt. Areas below 25 ppt or experiencing extended drops in salinity do not support growth or survival rates necessary for productive aquaculture. The purpose of this study was to better understand the molecular response of the hard clam to low salinity stress. In the spring of 2019 and 2021, the VIMS Eastern Shore Laboratory secured unique hard clam lines representative of the genetic diversity across the natural range along the US east coast. Salinity treatments of 35 ppt and 15 ppt were conducted for 26 hours in the summer of 2021 with two different age groups from eight clam lines. RNA sequencing data from either gill tissue (adults) or pooled whole-body tissue (juveniles) were used to assess the transcriptomic response of clams to short-term low salinity stress. This study found 545 genes in adult gills and 465 genes in juvenile whole-bodies that were significantly differentially expressed when clams were exposed to a salinity of 15 ppt versus 35 ppt. Heat shock, apoptosis, and cellular polarity genes were among the significantly differentially expressed genes, based on a log2 fold change > 1 and a false discovery rate < 0.05, and were both up and down regulated in response to 15 ppt versus 35 ppt. Pathways, including protein processing in the endoplasmic reticulum and fluid shear stress, were significantly enriched in response to 15 ppt versus 35 ppt. These results improve the understanding of how hard clams respond to low salinity stress and provide a foundation for further exploration of low salinity tolerance in hard clams to benefit the aquaculture industry.